Nigeria : 2007 Article IV Consultation; Staff Report; Staff Supplement and Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2008)
The success of Nigeria's reforms brings new policy challenges for preserving and building on the reform gains. The immediate challenge is to enshrine a fiscal institution that ensures that fiscal policy is consistent with macroeconomic stability. Nigeria's integration into the global economy brings new challenges for ensuring financial stability. Monetary policy has strengthened. The balance of payments outlook is consistent with external stability. Non-oil sector growth can only be sustained with supportive macroeconomic policies and a resolution of the infrastructure gap.